The Economic Functions of Cross-Border Activities of Skouw Sae Community, Jayapuraconomic Functions of Cross-Border Activities of Skouw Sae Community, Jayapura - Usman, La (Universitas Negeri Semarang, 2017)
This article aims to illustrate the economic functions of cross-border done by Skouw Sae community residents, Muara Tami District, Jayapura City to Wutung Vanimo Village, Papua New Guinea (PNG) using ethnographic approach. This study reveals seven economic functions of cross-border activity. These seven functions include fulfilling the family’s nutritional needs of a long-term food preparation idea system, apprehending the meaning of the land as a source of life, meeting the needs of salvation through protection and defense of religion through purchasing beverages for Christmas and leaving the idea system of Jesus Christ as the source Love, fulfilling the need for relaxation through school vacation activities and inheriting the idea system of the need for a refresher to familiarize the family, meeting the needs of the movement through village leaders’ visits to bring the leaders of the two communities together and inherit the idea system of formal and symbol leaders, meeting the needs of growth through traditional educational activities within the family and inheriting a system of ideas for the necessity of teaching for men. In conclusion, the economic function of cross-border activity is not only done to fulfill basic needs, but also the institutional needs and symbolism of local residents.